New Monoterpenoid Indoles with Osteoclast Activities from Gelsemium elegans - Xin Wei; Rui Guo; Xiao Wang; Jia-Jun Liang; Hao-Fei Yu; Cai-Feng Ding; Ting-Ting Feng; Li-Yan Zhang; Xia Liu; Xin-Yue Hu; Ying Zhou (Molecules, 2021)
The well-known toxic medicine Gelsemium elegans is widely and historically used to treat bone fracture and skin ulcers by the folk people of China. Two new monoterpenoid indole alkaloids, gelselegandines D and E, together with the known analogue gelegamine A were isolated from G. elegans. Their structures were elucidated by means of spectroscopic techniques and quantum chemical calculations. All isolated compounds were tested for the effects on RANKL-induced osteoclast formation. Interestingly, gelselegandine E and gelegamine A, respectively, showed significant promoting and inhibitory activities on osteoclastogenesis, while gelselegandine D had no activity under the same concentration. This work suggested the different configurations for the carbons near the C-19/20 oxygen rings of the isolated compounds may be the key active groups on osteoclast formation and provided the evidence for the rationality as the traditional treatment for bone-related diseases of G. elegans.